2013
DOI: 10.1371/journal.pone.0068057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Obstructive Sleep Apnoea on Fetal Growth: A Prospective Cohort Study

Abstract: ObjectiveThe objective of this study is to determine whether obstructive sleep apnea (OSA) is associated with reduced fetal growth, and whether nocturnal oxygen desaturation precipitates acute fetal heart rate changes.Study DesignWe performed a prospective observational study, screening 371 women in the second trimester for OSA symptoms. 41 subsequently underwent overnight sleep studies to diagnose OSA. Third trimester fetal growth was assessed using ultrasound. Fetal heart rate monitoring accompanied the slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 40 publications
2
115
0
1
Order By: Relevance
“…Of the two studies that used PSG-based diagnoses of SDB, one was a retrospective cohort study23 that showed no association and the other, a large database study22 demonstrated a positive association. One recent small study by Fung et al used PSG to study 51 pregnant women and identified 14 with sleep apnoea, which was associated with delivering babies with impaired fetal growth 41. These authors also used customised birthweight centiles to define SGA, but found a significant association between sleep apnoea and impaired fetal growth (defined as either a birth weight <10th centile or fall in customised centile >33% between 32 weeks and term) but not SGA defined by birth weight <10th centile alone 41.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two studies that used PSG-based diagnoses of SDB, one was a retrospective cohort study23 that showed no association and the other, a large database study22 demonstrated a positive association. One recent small study by Fung et al used PSG to study 51 pregnant women and identified 14 with sleep apnoea, which was associated with delivering babies with impaired fetal growth 41. These authors also used customised birthweight centiles to define SGA, but found a significant association between sleep apnoea and impaired fetal growth (defined as either a birth weight <10th centile or fall in customised centile >33% between 32 weeks and term) but not SGA defined by birth weight <10th centile alone 41.…”
Section: Discussionmentioning
confidence: 99%
“…Fung et al [46] failed to find a difference in birth weight or SGA in their small cohort. However, when plotting fetal size at 32 weeks' gestation compared to birth centile, they did find that fetal growth trajectory fell across centiles in late pregnancy in women who had OSA.…”
Section: Sdb and Delivery Outcomesmentioning
confidence: 85%
“…Most studies that have longitudinally recruited women fail to find a relationship between maternal OSA and birth weight [46,47], SGA [46][47][48][49], or LGA [48]. Different polysomnographic systems were used across these studies and definitions of OSA varied by study.…”
Section: Sdb and Delivery Outcomesmentioning
confidence: 99%
“…Several studies and a meta-analysis suggest that OSA is associated with adverse perinatal outcomes, particularly when associated with hypertensive disorders of pregnancy which are major causes of maternal and fetal morbidity and mortality and result in significant healthcare expenditure. [1][2][3][4][5] Physicians and other healthcare providers who care for pregnant women should recognize symptoms and risk factors for OSA to enable effective screening. Research is needed to evaluate valid screening tools in the pregnant population.…”
mentioning
confidence: 99%